Development of Mobile Application M-Epier Using MDA Framework - Sri Puji Utami A; Puspa Setia Pratiwi; Nurmaya Nurmaya (Syntax Literate, 2022)
In this study, a mobile application, named M-Epier (Mobile Career Explorationr, which works on Android devices. In particular, this app aims for career development and exploration questionnaire as the measuring too, as well as for increasing knowledge and awareness about the career environment. This application development applies the concept of gamification with the MDA (Mechanics Dynamics Aesthetics) Framework. With that being said, gamification makes users become more motivated to do the questionnaires and the user experience more enjoyable. The system testing is done using the UEQ (User Experience Questionnaire) with a sample of 30 respondents aged 17 to 20 years old. The test results are positive for each UEQ scale with an average value of ‘excellent’. Meanwhile, the functional testing uses questionnaire with 25 input and output scenarios which results in overall value of ‘valid’. This shows that both in terms of appearance and function M-Epier is in accordance with the needs of users.